2010
DOI: 10.1002/app.31850
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and mechanical properties of polyketone/polyamide polymer alloys

Abstract: ABSTRACT:We have investigated polyketone (PK)/ polyamide 6 (PA) polymer alloys having enhanced Charpy impact energy greater than that of polycarbonate (PC) as a result of moisture absorption. From the results of differential scanning calorimetry (DSC), Raman spectroscopy, and transmission electron microscope (TEM) observation of the polymer alloys, it was found that PK-rich and PA-rich phases exist at the nanometer level in the polymer alloys; however, a microscopic interaction phase formed between the two pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Figures and are the SEM photos of cryofractured surface of PK, SAN, and their blends at various compositions. The cryofractured surfaces of PK show ductile characteristics (i.e., deformed and rough surface) while fracture surfaces of SAN40 and SAN48 show brittle features (i.e., clean and smooth surface) (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…Figures and are the SEM photos of cryofractured surface of PK, SAN, and their blends at various compositions. The cryofractured surfaces of PK show ductile characteristics (i.e., deformed and rough surface) while fracture surfaces of SAN40 and SAN48 show brittle features (i.e., clean and smooth surface) (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…Kato and co‐workers surprisingly found that the absorption of moisture markedly improved the impact strength of POK/PA6 blends. The water‐absorbing amorphous phase of PA6 played an important role in enabling POK/PA6 blends to exhibit high impact strength and toughness, which was over 150 kJ m −2 and even close to 200 kJ m −2 , whereas the value under a dry condition was less than 50 kJ m −2 . TEM results revealed that the POK/PA6 alloys show a characteristic microstructure consisting of the PA6‐rich phase and a lamellar network of the POK‐rich phase, as shown in Fig.…”
Section: Polyketone Blendsmentioning
confidence: 92%
“…42,43 Elastomer-toughened polymer blends, while increasing toughness, generally lead to deterioration of tensile strength and stiffness. However, blending of POKs with PAs including amorphous PAs 44,45 and semi-crystalline ones [46][47][48] resulted in toughened POK materials with good structural strength and ductility.…”
Section: Binary Blends Of Polyketone Toughened Polyketone Blendsmentioning
confidence: 99%
“…Favorable properties such as high tensile strength, high wear resistance, low gas permeability and high chemical resistance give EPCO great potential as an engineering plastic and a barrier packaging material. [1][2][3][4][5][6][7][8][9] However, control of the temperature to below 240°C is recommended for the melt fabrication process of EPCO because thermal degradation occurs readily at a higher temperature. [10][11][12][13][14] This is a result of residual palladium, the polymerization catalyst, for EPCO, which frequently causes trouble in the melt processing of EPCO because of a very narrow processing window.…”
Section: Introductionmentioning
confidence: 99%